Effects of low-cost offsets on energy investment new perspectives on REDD- - Sabine Fuss; Alexander Golub; Jana Szolgayova; Michael Obersteiner (Fondazione Eni Enrico Mattei (FEEM), 2009)
Tropical deforestation is one of the major sources of carbon emissions, but the Kyoto Protocol presently excludes avoiding these specific emissions to fulfill stabilization targets. Since the 13th Conference of the Parties (COP) to the UNFCCC in 2007, where the need for policy incentives for the reduction of emissions from deforestation and degradation (REDD) was first officially recognized, the focus of this debate has shifted to issues of implementation and methodology. One question is how REDD would be financed, which could be solved by integrating REDD credits into existing carbon markets. However, concern has been voiced regarding the effects that the availability of cheap REDD credits might have on energy investments and the development of clean technology. On the other hand, investors and producers are also worried that emissions trading schemes like the one installed in Europe might deter investment into new technologies and harm profits of existing plants due to fluctuations in the price of emissions permits. This paper seeks to contribute to this discussion by developing a real options model, where there is an option to invest in less carbon-intensive energy technology and an option to purchase credits on REDD, which you will exercise or not depending on the future evolution of CO2 prices. In this way, unresolved questions can still be addressed at a later stage, while producers and investors hold REDD options to maintain flexibility for later decisions. We find that investment in cleaner technology is not significantly affected if REDD options are priced as a derivative of CO2 permits. Indeed, the availability of REDD options helps to smooth out price fluctuations that might arise from permit trading and thus decreases risk for the producer - thereby being a complement to permit trading rather than an obstacle undermining cap-and-trade.
Keywords: Q23; Q28; 330; Real Options; Energy Investment; Cap-And-Trade; REDD